The science of social vision - Adams, Reginald B. (New York ; Oxford : Oxford University Press, 2011)
The human visual system is particularly attuned to and remarkably efficient at processing social cues. This text examines the functional and neuroanatomical mechanisms which underpin social vision.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: Visual perception -- Social aspects; Social perception; Social interaction